Systematic political geography. 4th edition - Glassner, M.I.; De Blij, H.J. (Systematic political geography. 4th edition, 1988)
The fourth edition of this text has been thoroughly updated and includes expanded chapters on Antarctica and outer space as well as new chapters on the geography of elections and the geography of war and peace. A chapter is devoted to outlaws and merchants of death which covers piracy, drug trafficing, the arms trade, and terrorism. Other additions include coverage of international economic sanctions, transnational corporations, refugees, and pollution across international boundaries. -from Publisher
Keywords: arms trade; dept.egm; economic sanctions; elections; peace; political geography; pollution; refugees; terrorism; war; ⛔ No DOI found

On whittlesey, bowman and harvard - Martin, Geoffrey J (Annals of The Association of American Geographers, 1988)
Keywords: dept.egm

Preston E. James, 1899–1986 - Martin, Geoffrey J (Annals of The Association of American Geographers, 1988)
Keywords: dept.egm